Valoración económica del carbono almacenado en la biomasa aérea de Cedrelinga Cateniformis de la concesión forestal Hydra Consulting distrito de Pebas Loreto 2022 - Cordova Pisco, Erik Duvalier (2025)
The study "Economic Valuation of Carbon Stored in the Aboveground Biomass of Cedrelinga cateniformis in the Hydra Consulting Forest Concession, Pebas District, Loreto, 2022" was conducted in the Hydra Consulting Forest concession, located in the Pebas district, Ramon province, Loreto department, Peru, during 2022. The results revealed a significant volume of Cedrelinga cateniformis forest, with a total of 4,960 m3/ha in the study area and 2,479,828 m3 across the entire concession. It was estimated that the carbon stored in the aboveground biomass of Cedrelinga cateniformis amounted to 2511.02 tC/ha, totalling 1,255,510 tC across the concession. Additionally, the price of carbon stored in the species' aboveground biomass reached S/. 29,780.450 per hectare, summing up to S/. 14,890,225.00 across the concession. A significant positive correlation (Spearman correlation coefficient of 0.98) was found between carbon stored by diameter class and carbon price. These findings underscore the importance of conserving and sustainably managing Cedrelinga cateniformis forests to maximize their contribution to carbon sequestration and economic value. In conclusion, this study provides valuable information for decision-making in forest management and contributes to the understanding of economic valuation of carbon in Amazonian forests of Peru.